Processing of metallic fiber hybrid spun yarns for better electrical conductivity. Issue 9 (4th July 2019) - Shahzad, Amir; Rasheed, Abher; Khaliq, Zubair; Qadir, Muhammad Bilal; Khan, Muhammad Qamar; Hamdani, Syed Talha Ali; Ali, Zulfiqar; Afzal, Ali; Irfan, Muhammad; Shafiq, Muhammad; Kim, Ick Soo
ABSTRACT: This research was aimed at processing of metallic fiber hybrid spun yarns consisting of polyester/stainless steel and viscose/stainless steel staple fibers to achieve better electrical conductivity. Conventional ring spinning machine and ring twister machine were used to produce the single and plied yarns respectively. The linear electrical resistance of yarns was analyzed with reference to the three levels of twist multiplier (TM) for same yarn count, three levels of yarn fineness (Ne) at the same TM level, and number of plies for the same final yarn count. These results showed that by increasing twist, the electrical conductivity of yarn was increased. However, yarn fineness was in inverse relation with the electrical conductivity of yarns. The effect of yarn plying and twisting to produce the Ne 10s yarn was also found critical in governing the electrical properties. The electrical conductivity of viscose and stainless steel hybrid yarn was found more sensitive to increase with an increase in relative humidity contrary to that of polyester and stainless steel hybrid yarns. The findings of the study are significant to produce the hybrid spun conductive yarns for their potential applications in a variety of tailor-made functional, protective and smart textiles.